2006
DOI: 10.1603/0022-0493-99.4.1420
|View full text |Cite
|
Sign up to set email alerts
|

Is Polyandry a Common Event Among Wild Populations of the Pest <I>Ceratitis capitata</I>?

Abstract: In many insect species, females can mate more than once and store sperm from more than one male. An assessment and understanding of polyandry in the field can be important for pest species with a high colonization potential, such as the Mediterranean fruit fly, Ceratitis capitata (Wiedemann), which is also highly polyphagous and among the most destructive agricultural insects. The use of polymorphic microsatellite markers, combined with different statistical approaches, provides evidence that polyandry occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Some field studies reported percentages of double mating in wild females: up to 50% [ 34 ]; less than 28% [ 35 ]; 4% to 28% [ 67 ]. Laboratory tests reported by Abraham et al [ 31 ] indicated 20% re-mating for females mated with 100Gy-irradiated males.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some field studies reported percentages of double mating in wild females: up to 50% [ 34 ]; less than 28% [ 35 ]; 4% to 28% [ 67 ]. Laboratory tests reported by Abraham et al [ 31 ] indicated 20% re-mating for females mated with 100Gy-irradiated males.…”
Section: Resultsmentioning
confidence: 99%
“…This parameter has been repeatedly studied in the laboratory with various estimates. However, analysis of field-sampled females progeny showed less than 28% [ 35 ] or 50% [ 34 ] multiple mating. It is thus possible to roughly estimate a percentage of female daily re-mating proportion: in average, between 7% and 12%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations